PENERAPAN MODEL PEMBELAJARAN TIME TOKEN UNTUK MENINGKATKAN KETERAMPILAN KOMUNIKASI PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS V - Khairiyatun Nisa’; M. Syahrul Rizal; Rizki Ananda; Putri Hana Pebriana; Afriza Rahma Rani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The research is motived by the low communication skills of students in class V. This study aims to improve the communication skills of students in class V UPT SDN 013 Kumantan. This research is classroom action research, which was carried out in two cycles and each cycle consisted of two meetings. The subjects in this research were 1 teacher and 9 students, while the object was through the application of the time token learning model to improve students' communication skills. This research instrument consists of teacher observation sheets, student observation sheets, documentation sheets and communication skills observation sheets during learning through the application of the time token learning model. Meanwhile, the data analysis technique used is qualitative and quantitative descriptive analysis. The success in implementing this time token learning model can be seen based on the results of observation in the initial data, which was 59.1, decreasing in cycle 1, meeting 1, amounting to 56.3, then increasing again in meeting 2 to 60.5. Cycle II, meeting 1, was 70.2, then increased again in meeting 2 to 82,1, as well as classical completeness from the initial data of 33.3%, then in cycle I, meetings 1 and 2, by 33,3% and 33,3%. In cycle II, meeting 1, it was 55,5% and in meeting 2 it increased again to 88.8%. thus, it can be concloud that applying the time token learning moden can improve the communication skills of fifth graders at UPT SDN 013 Kumantan